Human Error dalam Berkendara Berdasarkan Kebiasaan Pelanggaran oleh Pengemudi - Lovely Lady; Ani Umyati (Institut Transportasi dan Logistik Trisakti, 2021)
Human error is an insistety action that can reduce the effectiveness, safety, and performance of a system. Human error can be caused by unsafe acts that are the type of errors committed by the subject of the perpetrator due to errors or violations of procedures. This study aims to identify human error in driving based on the type of deviation that is often done by the driver and analyze the influence of age and gender on traffic irregularities. Data collection using Driver Behavior Questionaire (DBQ). There were 325 respondents who filled out the questionnaire, 72.31% of male and 27.69% of female respondents with an age range between 18 to 65 years. The questions in the questionnaire were compiled based on the group of deviations made by the driver, there are four types of wrong habits in driving, namely errors, lapse, violations, violation, and aggresive violations. Lapse is an error that frequent committed by the driver. The adolescent group committed higher offences than the adult and middle age groups for all types of traffic irregularities. The male were significantly more likely to commit violation (a=0.00) and aggresive violations (a=0.014) than female. Both types of violations conscious committed by the driver to achieve a specific goal.